A study of nucleon unstable states produced in direct nuclear reactions - Hartmann, Kurt Miklos (Department of Physics, 2016)
We study excited states of a nucleus that are unstable against nucleon decay. An expression is derived for the wave function of such an excited nucleus, using the continuum shell-model theory. The bound and resonant states of the shell-model Hamiltonian are treated on an equal footing. The resonant part of this wave function is substituted into the DWBA transition amplitude for stripping reactions. Simple expressions are obtained for the energy spectrum and angular distribution of the uncaptured nucleon(s). Comparison with the corresponding elastic scattering cross section is made and the extraction of· spectroscopic information is discussed. Angular distributions and excitation functions for a number of projectile-target systems are calculated. We also suggest nucleon induced inelastic scattering as an alternative direct reaction mechanism with which these excited states may be studied.